Impact of pulmonary hypertension and congenital heart disease with hemodynamic repercussion on the severity of acute respiratory infections in children under 5 years of age at a pediatric referral center in Colombia, South America (2020)
Acute respiratory infection is one of the main causes of morbidity in children. Some studies have suggested that pulmonary hypertension and congenital heart disease with haemodynamic repercussion increase the severity of respiratory infections, but there are few publications in developing countries. Methods: This was a prospective cohort study evaluating the impact of pulmonary hypertension and congenital heart disease (CHD) with haemodynamic repercussion as predictors of severity in children under 5 years of age hospitalised for acute respiratory infection. Results: Altogether, 217 children hospitalised for a respiratory infection who underwent an echocardiogram were evaluated; 62 children were diagnosed with CHD with haemodynamic repercussion or pulmonary hypertension. Independent predictors of admission to intensive care included: pulmonary hypertension (RR 2.14; 95% CI 1.06–4.35, p = 0.034), respiratory syncytial virus (RR 2.52; 95% CI 1.29–4.92, p = 0.006), and bacterial pneumonia (RR 3.09; 95% CI 1.65–5.81, p = 0.000). A significant difference was found in average length of hospital stay in children with the cardiovascular conditions studied (p = 0.000). Conclusions: Pulmonary hypertension and CHD with haemodynamic repercussion as well as respiratory syncytial virus and bacterial pneumonia were predictors of severity in children with respiratory infections in this study. Early recognition of cardiovascular risks in paediatric populations is necessary to lessen the impact on respiratory infections.